2022
DOI: 10.1002/adhm.202101983
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Ion Implantation Improving Cell Adhesion on Titanium Surfaces through Increased Attraction of Fibronectin PHSRN Domain

Abstract: Mechanistic understanding of fibronectin (FN) adsorption which determines cell adhesion on cell-implant interfaces is significant for improving the osteoconduction and soft-tissue healing of implants. Here, it is shown that the adsorption behavior of FN on the titanium oxide surface (TiO 2 ) is highly relative to its Pro-His-Ser-Arg-Asn (PHSRN) peptide. FN lacking PHSRN fails to bind to surfaces, resulting in inhibited cell adhesion and spreading. Molecular dynamics simulation shows higher affinity and greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Biomaterials with a high surface energy are beneficial for protein adsorption in a micro-environment that subsequently attracts osteogenic cells for new bone formation/bone-bonding. 29 Compared with PT20 and PI, PT40 with a high Ta content exhibited a higher surface energy. The hydrophilic surface with high surface energy facilitates the initial blood contact and protein adsorption, which further attracts cell attachment and boosts cell multiplication.…”
Section: Resultsmentioning
confidence: 92%
“…Biomaterials with a high surface energy are beneficial for protein adsorption in a micro-environment that subsequently attracts osteogenic cells for new bone formation/bone-bonding. 29 Compared with PT20 and PI, PT40 with a high Ta content exhibited a higher surface energy. The hydrophilic surface with high surface energy facilitates the initial blood contact and protein adsorption, which further attracts cell attachment and boosts cell multiplication.…”
Section: Resultsmentioning
confidence: 92%
“…The cumulative release profile in Figure 9 C proved that the release of Ag ions was very fast during the first 6 h of incubation in the presence of the V8 enzyme. The wettability studies ( Figure 9 D) showed that the LBL@MSN-Ag coating on the Ti was hydrophilic with a contact angle of 12.4°, which resulted in higher cell adhesion on the implant’s surface [ 101 ]. As shown in Figure 9 E, the number of viable bacterial colonies on the LBL@MSN-Ag treated Ti were significantly lower than that of the untreated Ti implant, showing the high antibacterial ability of the EZRH coatings in vivo.…”
Section: Biomolecule-responsive Hydrogelsmentioning
confidence: 99%
“…Previous studies have attributed macrophage responses to differences in the protein layers adsorbed on the implant surface. [22,23] When a dental implant enters the body, it is surrounded by blood. Those proteins come in contact with the implant forming a protein layer based on the surface physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%